Phase assemblage and properties of laser cladded TixCrFeCoNiCu high-entropy alloy coating on aluminum - Yanzhou Li; Yan Shi (Materials Research Express, 2020)
The Ti _x CrFeCoNiCu(x:molar ratio, ${\rm{x}}=0,\,0.2,\,0.5,\,0.8,\,{\rm{or}}\,1.0$ ) coating was depositd on aluminum by laser cladding. The phase structure, microstructure, hardness, wear resistance and corrosion resistance were studied. The results show that with the increase of Ti content, the phase structure of the Ti _x CrFeCoNiCu coating changes from single FCC to FCC + B2, and FCC + Laves phase. When Ti is increased to 1.0, cracks appear in the coating. The hardness of the Ti _x CrFeCoNiCu coating is enhanced with the increase of Ti content, and ranges from 215HV _0.2 to 585HV _0.2 , which is about 3 to 7 times that of the substrate. The strengthening mechanism of Ti _0.2 CrFeCoNiCu is solid solution strengthening, and when the Ti content is greater than 2, the strengthening mechanism of Ti _x CrFeCoNiCu coating is precipitation strengthening. The influence of Ti on the wear resistance exhibits the same trend as with hardness. When Ti increased from 0 to 0.8, the wear rate of the Ti _x CrFeCoNiCu coating changed from ${\rm{2.26}}× {{\rm{10}}}^{-{\rm{4}}}\,{{\rm{mm}}}^{{\rm{3}}}\,{{\rm{Nm}}}^{-1}$ to $9.92× {10}^{-7}\,{{\rm{mm}}}^{{\rm{3}}}\,{{\rm{Nm}}}^{-1}:$ smaller than the substrate. The addition of Ti increases the current corrosion density of Ti _x CrFeCoNiCu coating, but both coatings still exhibits superior corrosion resistance relative to the substrate.